Estudio de las cadenas operativas y la producción de la Alfombra artesanal en la parroquia El Rosario cantón Guano - Ramírez Satán, Janneth Abigail (2025)
The present research, entitled "Study of Operational Chains and the Production of Handcrafted Carpets in El Rosario Parish, Guano Canton," mainly analyzed the traditional processes involved in making artisanal carpets. It was conducted to evaluate the level of training local artisans possess regarding the knowledge and skills related to this art form. Furthermore, it sought to identify the main opportunities for improvement that could contribute to both the cultural and commercial strengthening of this craft. It is important to mention that this study was developed within the conceptual framework of operational chains, a notion proposed by Leroi-Gourhan, who suggested that artisanal techniques are cultural manifestations that preserve the history and worldview of a community. Each stage of production was described in detail, starting from the selection and preparation of raw materials, such as the shearing of sheep to obtain wool and subject it to the appropriate treatment through washing, carding, and spinning, which are still performed manually using ancestral methods. The study narrated the weaving techniques used in looms, which are rich with cultural meanings; it explained how the finishing processes ensure the quality and durability of each piece. A qualitative methodology was employed to gather the information based on interviews with six artisans from El Rosario Parish. These artisans generously shared their knowledge and experiences related to their daily work in carpet production. Direct observation was used to validate the coherence of the responses in the workshops of each artisan to record the working conditions and tools used during the production. This research revealed that artisans possess knowledge passed down through generations. However, they face serious challenges, such as the shortage of local raw materials, unfair competition from imported industrial products, fragile workshop infrastructure, and limited technical and commercial training access. Consequently, the study concludes that the production of carpets in 'El Rosario' goes far beyond mere economic activity. It represents a living cultural heritage encapsulating ancestral knowledge and unique artisanal techniques. It is recommended that policies be created and implemented to protect and strengthen Guano's textile craftsmanship, ensuring that artisan families' cultural legacy is preserved and promoted for future generations